De novo transcriptome assembly of the Perna viridis: A novel invertebrate model for ecotoxicological studies - V. G. Vysakh; Sandhya Sukumaran; Gopalakrishnan A. (Scientific Data)
Abstract Mussels, particularly Perna viridis, are vital sentinel species for toxicology and biomonitoring in environmental health. This species plays a crucial role in aquaculture and significantly impacts the fisheries sector. Despite the ecological and economic importance of this species, its omics resources are still scarce. We generated a gill-specific reference transcriptome for Perna viridis using 292 million short Illumina reads from eight pooled gill tissue samples isolated from twenty-four individuals. The Trinity assembler generated 438,842 transcripts with an N50 of 1,958 bp. Several databases were employed in the annotation process. This dataset greatly expands the omics resources of bivalve databases and advances our knowledge of transcriptomics, molecular biology, environmental toxicology, and cancer research.